DESCEMET MEMBRANE ENDOTHELIAL KERATOPLASTY (DMEK): CLINICAL OUTCOME OF THE FIRST 52 CONSECUTIVE CASES PERFORMED IN 2022 AND 2023: Descemet membrane endothelial keratoplasty (DMEK) - Jovanović, Vesna; Ignjatović, Zora (Srpski medicinski časopis Lekarske komore, 2026)
Introduction/Objective: Corneal endothelial dysfunction is the most frequent indication for corneal transplantation in the developed countries. Shortly after its first appearance, Descemet membrane endothelial keratoplasty (DMEK) has been widely accepted due to its numerous advantages. Our aim is to report clinical outcome of DMEK in patients with dysfunction of corneal endothelium. Material and method: We analyzed clinical outcome of DMEK of the first 52 consecutive cases. Parameters analyzed were as follows: best corrected visual acuity (BCVA), tomography, central corneal thickness, anterior segment optical coherent tomography (AS-OCT), and posterior segment OCT where needed. All parameters were measured before and up to six months after the surgery. Results: DMEK was successful in 46 out of 52 eyes that underwent surgery. All eyes (100%) with good visual potential reached BCVA ≥ 20/40, and 57% reached ≥ 20/25. A partial graft detachment occurred in 8 eyes, which after repeated air injection into the anterior chamber resulted in graft reattachment and a clear cornea. Six eyes experienced primary graft failure which required second surgery. Conclusion: Our series showed an excellent outcome of DMEK, concerning the rate of visual rehabilitation and potential serious complications. The main complication was an early partial graft detachment, which did not affect the final surgical outcome.